Design as a learning opportunity in biology lessons—a cross-domain STEM approach and its impact on biological subject knowledge - Reiser, Markus; Binder, Martin; Weitzel, Holger (Frontiers in Education, 2024)
There is a broad consensus in politics, economy and science about the importance of promoting STEM competences. To promote STEM skills in the classroom, we propose a cross-domain approach combining the STEM sub-domains of Biology and Technology/ Engineering. Therefore, we have developed a model that illustrates how the STEM sub-domains of Biology and Technology/ Engineering can complement each other in a cognitive process. Both sub-domains show similarities in working methods and consider structural and functional relationships. These synergies can be brought together in a design process. This approach leads to the question of the extent to which a cross-domain approach utilising a design process can be a learning opportunity for biological subject knowledge. Based on this model, we have created a learning arrangement on the topic of the "locomotor system". Learners should use a design process to build a feeding machine inspired by structural-functional relationships in different locomotor systems. In a quasi-experimental study, we compared this Design approach with two alternative teaching approaches (a Reconstruction approach and a Biology approach). In the Reconstruction approach, students receive the same input on structural-functional relationships in locomotor systems but build their feeding machine according to a predetermined plan. In the Biology approach, no feeding machine is built; instead, structural-function relationships in locomotor systems are modelled using further examples from the animal world. 413 pupils (age: M = 12.53, SD = 0.818) took part in the study. Longitudinal and cross-sectional analyses emphasise the potential of the Design approach compared to the other methods and show significant differences in long-term learning outcomes. Path models illustrate that cognitive abilities (IQ) and participation in the "Design"-intervention group are decisive prerequisites for learning success. The results also show that students following the Design- approach develop a significantly improved understanding of concepts related to the musculoskeletal system. Using a design process combining biology and engineering presents a learning opportunity for students to develop long-term robust biological knowledge and understanding of biological concepts. Thus, using a design approach can be a cross-domain bridge for integrated STEM instruction in order to foster pupils’ knowledge acquisition and competences